Um ecumenismo do espírito: o diálogo católico-pentecostal como fruto da ecumenicidade conciliar - Leite, Huanderson Silva (2021)
Christian unity is one of the greatest challenges facing the Church today. As you can believe in the Gospel announced, if our division does not allow us to overcome differences in the name of what characterizes us as Christians, which is love, because “this is what they will know that you are my disciples. If you love one another ”(cf. Jn 13:35). Greater than what divides us is what unites us: Christ Himself. It must be the point of convergence for the understanding of all Christians. In the 20th century, through the ecumenical movement, many people uncomfortable with this situation of division arose to fight for unity, and it is from them and their initiatives that the ecumenical movement emerges, a movement that collaborates and influences in a spectacular way the Second Vatican Council, although in its early days the Catholic Church was averse to it. The conciliar spirit of renewal, openness and unity placed the Church in a position of dialogue with society, with other religions and with other Christian expressions. The conciliar ecclesiology of the Dogmatic Constitution Lumen Gentium recognizes the Church as a Temple of the Holy Spirit and a reality adorned with hierarchical and charismatic gifts, and this data will allow the Catholic Church to put itself in a position of dialogue with Pentecostalism, which, in turn, was born in a reality parallel to the ecumenical movement, but which, due to several factors, has distanced itself from it throughout history. From a common heritage, thanks to conciliar ecumenicity, an “ecumenism of the Spirit” or spiritual ecumenism between Catholics and Pentecostals becomes possible, and thus, perhaps, in the realities in which, in recent times, the dialogue had been more complex, the even it becomes possible and, consequently, Catholics and Pentecostals bear witness to the world that unity is possible, it is the work of the Spirit and the desire of the Lord Jesus (cf. Jn 17:21)